2015
DOI: 10.1186/s13073-015-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeted high-throughput sequencing for genetic diagnostics of hemophagocytic lymphohistiocytosis

Abstract: BackgroundHemophagocytic lymphohistiocytosis (HLH) is a rapid-onset, potentially fatal hyperinflammatory syndrome. A prompt molecular diagnosis is crucial for appropriate clinical management. Here, we validated and prospectively evaluated a targeted high-throughput sequencing approach for HLH diagnostics.MethodsA high-throughput sequencing strategy of 12 genes linked to HLH was validated in 13 patients with previously identified HLH-associated mutations and prospectively evaluated in 58 HLH patients. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Presumably they are not clinically neutral given their enrichment in patients with secondary HLH compared to healthy or inflammatory controls (Zhang et al, 2008a;Vastert et al, 2010;Kaufman et al, 2014). Only one study reported no enrichment of monoallelic rare variants in secondary HLH, compared to a large healthy control cohort (Tesi et al, 2015b). Theoretically, hypomorphic single-copy mutations may alter protein levels and thus induce subtle impairment of cytotoxicity, increasing susceptibility to infections.…”
Section: A Blurring Distinction Between Primary and Secondary Hlhmentioning
confidence: 97%
See 1 more Smart Citation
“…Presumably they are not clinically neutral given their enrichment in patients with secondary HLH compared to healthy or inflammatory controls (Zhang et al, 2008a;Vastert et al, 2010;Kaufman et al, 2014). Only one study reported no enrichment of monoallelic rare variants in secondary HLH, compared to a large healthy control cohort (Tesi et al, 2015b). Theoretically, hypomorphic single-copy mutations may alter protein levels and thus induce subtle impairment of cytotoxicity, increasing susceptibility to infections.…”
Section: A Blurring Distinction Between Primary and Secondary Hlhmentioning
confidence: 97%
“…Theoretically, hypomorphic single-copy mutations may alter protein levels and thus induce subtle impairment of cytotoxicity, increasing susceptibility to infections. Interestingly, heterozygous mutations in PRF1 and LYST have also been implicated in severe H1N1 influenza (Schulert et al, 2016), suggesting the sequence variants are not strictly recessive but may generate haploinsufficiency for cytotoxicity genes (Zhang et al, , 2014aTesi et al, 2015b;Cetica et al, 2016).…”
Section: A Blurring Distinction Between Primary and Secondary Hlhmentioning
confidence: 97%
“…30,40 Besides, there is no evidence of an increase in rare, putatively pathogenic monoallelic variants in HLH-associated genes in secondary HLH patients so far analyzed. 41 Prospective studies analyzing the different HLH-related genes systematically and the combination of the genes' variants in large cohorts of secondary HLH patients, should help in evaluating the contribution of this genetic mechanism in conferring a greater risk in developing HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Next‐generation sequencing of different cohorts of subjects with primary immunodeficiency or hemophagocytic lymphohistiocytosis (HLH) reported least eight AP3B1 variants (Table S4) in a heterozygous state with or without a variant in another (synergistic) gene. These findings suggest that heterozygous AP3B1 variants may contribute to an immunologic phenotype (Chi et al, 2018; Gallo et al, 2016; Gao, Zhu, Huang, & Zhou, 2015; Miao et al, 2019; Mukda et al, 2017; Tesi et al, 2015; Xu et al, 2017). These variants have not been reported in HPS subjects but were included in this report because they may cause HPS when occurring in a homozygous or compound heterozygous state.…”
Section: Introductionmentioning
confidence: 99%